Performance Indicators Development for Toll Road Minimum Services Standards in Indonesia - Makmur, Amelia (International Journal of Integrated Engineering, 2019)
During recent years the infrastructure sector has grown tremendously, particularly toll roads. Toll road sections spread across several provinces in Indonesia are managed by various Toll Road Operators with different management styles. In providing their services to the public, Government requires the operators to meet a certain Toll Road Minimum Service Standard. Unfortunately, some of the performance indicators do not meet this standard any longer. The purpose of this research was to obtain performance indicators. The basic performance indicators were obtained from literature review of previous Indonesian research, several benchmarked foreign countries, and from the government’s minimum service standard. Next to that a survey was conducted by collecting data through questionnaires to toll road users, operators, regulators, and experts. The result provides an overview of stakeholders’ interests in determining KPIs and SPIs. 20 KPIs and 11 SPIs were obtained. Based on the evaluation and trial test that was carried out, the performance indicators obtained from this research can be applied to develop toll road MSS performance indicators in Indonesia.